the role of antineutrophil cytoplasmic antibodies in patients with systemic lupus erthematosus - Made, mohammed S.; AL-Shamma, I; Mousawy, khalida M.; sheikhly, A. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: